Study on Energy Distribution Law and Numerical Simulation of Mining Roadway Surrounding Rock. (23rd June 2022) - Zhang, Guohua; Ju, Chao; Duan, Yanwei; Wang, Yiwei; Qin, Tao; Wu, Chengjia
Abstract : In underground engineering, the deformation and failure process of the surrounding rock of the roadway is always accompanied by the occurrence of energy. The study of the energy distribution law of the surrounding rock of the roadway plays an important role in its stability. This paper first theoretically analyzes the stress and energy distribution law of the surrounding rock of the roadway, then with the help of numerical simulation method, combined with the existing physical and mechanical parameters, based on the existing support parameters of Dongrong No. 2 Mine, gradually compares and analyzes the distribution of vertical stress and energy under the three support methods of no support, original support, and combined support, and the results found that the vertical stress distribution law under the three support methods is basically the same. High-stress areas appear on the two ribs of the roadway, and low-stress areas appear on the roof and floor. The range of high-stress areas from no support to combined support continues to decrease and becomes more evenly distributed. The energy distribution pattern is basically the same. The overall energy of the coal seam is high. There are high-energy areas at 2 m left and right of the roadway, and the roof and floor energy of the roadway is the smallest. The low energy area extends 5 m up and down, respectively. The range of high-energy areas from no support to combined support is shrinking, and the energy distribution is more uniform.